Determination of toxic metals in blood by x-ray fluorescence spectrometry. - Vaasjoki, R.; Rantanen, Jorma (Scandinavian Journal of Work, Environment & Health, 1975)
An application of X-ray fluorescence spectrometry for the analysis of various toxic metals (lead, cadmium, manganese, chromium, nickel, vanadium) in whole blood was studied, and two techniques for sample preparation (vacuum drying and nitric acid combustion) were compared. The acid combustion method appeared to be superior on the basis of the accuracy and precision of the determinations. The tungsten-target X-ray tube was suitable for determining manganese, nickel, and vanadium, the lowest limits of detection being 0.021 µg/ml, 0.035 µg/ml and 0.017 µg/ml, respectively, and the precisions being between 4.25 and 6.92%. The sensitivity and reproducibility for lead, cadmium, and chromium were unsatisfactory. A comparison between the recoveries of X-ray fluorescence and atomic absorption analyses demonstrated that the X-ray method is suitable for determining manganese, vandium, nickel, cadmium, and lead. The poor sensitivity of the X-ray method, however, restricts its practical use. For vandium the results obtained by X-ray fluorescence were superior to those measured by a colorimetric method. No significant differences were observed between the results of single component and multicomponent analyses at the metal concentrations usual in physiological and toxicological cases.
Keywords: acid combustion; atomic absorption; blood; cadmium; chromium; lead; manganese; nickel; spectrometry; toxic metal; vacuum drying; vanadium; whole blood; X-ray fluorescence; X-ray fluorescence spectrometry